Novel process routes towards the production of spherical polymer powders for selective laser sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Kloos, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (AIP Conference Proceedings, 2019)
Additive manufacturing processes allow the production of individualized and complex parts without the use of molds or tools. Especially powder and beam-based AM processes like selective laser sintering (SLS) of polymers are promising, although the choice of commercial SLS powders is very limited. To further extend the applications of SLS, new and cheap materials with good processability must be supplied. Within this contribution two innovative methods for production of spherical polymer micro particles for SLS are discussed: The first approach is a process chain applicable to a wide range of polymers consisting of wet grinding in a stirred media mill followed by rounding of the obtained irregularshaped particles in a heated downer reactor and subsequent dry coating of the spherical particles for improvement of powder flowability. It will be outlined for glass-filled PBT systems. The second approach is melt emulsification with subsequent dry coating. In this process a polymer melt is emulsified by elongational and shear stresses in a rotor stator device. The method is exemplified for polypropylene (PP). Both approaches allow for production of spherical polymer micro particles. The effect of flowability, shape and bulk density on the powders' processabilities in SLS is assessed.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Additive manufacturing; Melt emulsification; Polymer powder; Rounding